A Tentative Tamdy Orthonairovirus Related to Febrile Illness in Northwestern China. (1st July 2019) - Liu, Xiafei; Zhang, Xu; Wang, Zedong; Dong, Zhihui; Xie, Songsong; Jiang, Mengmeng; Song, Ruixia; Ma, Jun; Chen, Shouyi; Chen, Kuncai; Zhang, Haoji; Si, Xingkui; et al.
Abstract: Background: Many novel tick-borne viruses have been discovered by deep-sequencing technology in recent years; however, their medical significance is unknown. Methods: We obtained clinical data of a patient from Xinjiang, China. Possible pathogens were detected by metagenomic analysis; the causative pathogen Tacheng tick virus 1 (TcTV-1) was found and further confirmed by reverse transcriptase–polymerase chain reaction, viral culture, and sequence analyses. Epidemiological investigation was conducted in the local human population, domestic animals, and ticks by serological/molecular methods. Results: A 62-year-old woman with a history of tick bite in Qinghe, Xinjiang, presented with fever and rashes. These symptoms were relieved after clinical treatment. TcTV-1 (strain QH1) was isolated from the patient's cerebrospinal fluid, throat swabs, and urine on day 47 after illness onset. Although the blood and urine showed viral RNA positive on day 73 after illness onset, the virus was only isolated from urine. Serological detection revealed a virus neutralizing antibody titer of 1:40 and 1:80 on day 47 and 73 after illness onset, respectively. No coinfection with other pathogens was detected, suggesting TcTV-1 may be the potential causative pathogen. We detected anti–TcTV-1 antibodies (immunoglobulin G: 10.1%; immunoglobulin M: 4.8%) in the local human population. The viral RNA was also found in cattle (4.9%), sheep (9.2%), and ticks, including Dermacentor marginatus (14.3%), Dermacentor silvarum (11.8%), Dermacentor nuttalli (6.7%), and Hyalomma asiaticum (4.8%). Conclusions: TcTV-1 may be associated with a febrile illness syndrome, and epidemiological data of the virus in humans and animals necessitate disease surveillance of TcTV-1 infection in China. Abstract : A Tamdy orthonairovirus, Tacheng tick virus 1, was found to be associated with febrile illness in northwestern China, where viral RNA or antibodies against the virus were detected in humans and animals, necessitating further disease surveillance of the infection.